Review of H2S sorbents at low-temperature desulfurization of biogas - Pourzolfaghar, Hamed; Ismail, Mohd Halim Shah; Siajam, Shamsul Izhar (World Academy of Research and Publication, 2014)
This review surveys the sorbents that remove Hydrogen Sulfide (H2S) from the biogas generated at low-temperature ranges from different sources. Biomass feedstocks contain low percentages of protein-derived sulfur that is converted primarily into H2S, as well as small amounts of carbonyl sulfide (COS) and organosulfur compounds during fermentation, gasification, etc. These sulfur species must be removed from the raw biogas before it is being used for the downstream fuel synthesis or the power generation because of their disadvantages, among which, acid rains, and human health problems. Several types of sorbents and ceria have been developed over the last two decades which are capable of removing H2S from the biogas at low-temperature ranges. This study has divided the current sorbents into three main categories on the basis of the recent investigations; (1) Activated carbons, (2) Metal based materials, and (3) Microporous and mesoporous silica. Further improvement is essential to develop sorbents appropriating them for desulfurization of the biogas owing to their low efficiency and high price, which present different challenges to eliminate hydrogen sulfide at low-temperature ranges.